Answer:
x= 1/20
Step-by-step explanation:
-1/2x = -10
multiply by 2x on each side
2x(-1/2x) = -10*2x
-1 = -20x
divide by -20
-1/-20 = -20x/-20
1/20 =x
Answer:
64
Step-by-step explanation:
Each side length is being multiplied by 8
Answer:
96
Step-by-step explanation:
Answer:
the integer is 5
Step-by-step explanation:
x^2+3(x+1)=43
x^2+3x+3=43
x^2+3x+(9/4)=43-3+(9/4)
(x+(3/2))^2=42 1/4
x+(3/2)=sqrt(42 1/4)
x+(3/2)=6 1/2
x=(6 1/2)-(3/2)
x=5
check:
5^2+3(6)=43
25+18=43
43=43
Did you mean this? <span>3^2x+1=3^x+5 => 3^(2x+1) = 3^(x+5)? If so, then 2x+1 is necessarily equal to x+5, so that 2x+1=x+5. Thus, x = 4 (answer).
Those parentheses are not optional; they must be part of your problem statement and solution.</span>